European Identity and Turkey’s Quest for the EU Membership - Erdem, Engin I. (International Studies. Interdisciplinary Political and Cultural Journal, 2017)
In the post-Single European Act period, debates around European identity have intensified, particularly in the context of EU enlargement. The EU’s move to being a supranational political entity in the past two decades has caused serious concerns in some sections of the elite and people across the EU member states. While French and Dutch rejections of the constitutional treaty set an important milestone, Turkey’s quest for the EU membership has complicated to a great extent controversies on European identity. The reviewed books here contribute to efforts to understand the extent to which European identity and Turkey’s bid for the EU membership has entangled. It is more likely to witness debates around both European identity and Turkey’s candidacy for the Union for many years to come; therefore, these books will more likely remain relevant for the academic and policy circles.